Hand selection in a preferential reaching task: The effects of object location, orientation, and task intention in preadolescent children. Issue 9 (11th August 2018) - Scharoun Benson, Sara M.; Forsyth, Amanda; Bryden, Pamela J.
Abstract: Introduction and Methods: Hand selection was assessed in preadolescent children (ages 9–11) within a preferential reaching task to delineate the effects of object location, orientation, and task intention on the assessment procedure and compared to data previously acquired from young adults. Results: The observed differences support the notion that children are still in a process of refining their movements in attempt to discern the most efficient and effective patterns of behavior. Notwithstanding differences in performance, similarities between preadolescents and young adults also emerged. Greater right‐hand selection in right space and when the handle was oriented to the right indicate that object proximity and orientation influence efficiency and thus constrain hand selection in unimanual object manipulation and role‐differentiated bimanual manipulation. Conclusions: Together, findings add to our understanding of hand preference, unimanual and bimanual object manipulation. Abstract : Hand selection was assessed in preadolescent children (ages 9–11) within a preferential reaching task to delineate the effects of object location, orientation, and task intention on the assessment procedure and compared to data previously acquired from young adults. The observed differences support the notion that children are still in a process of refining their movements in attempt to discern the most efficient and effective patterns of behaviour.